A study on relationship between income, inflation and stock market on demand for General takaful plan in Malaysia / Siti Nur Nadhira Muhammad Nafizon - Muhammad Nafizon, Siti Nur Nadhira (2013)
This study is to investigate the macroeconomic factors that influence the General takaful contribution in Malaysia. This study is to examine Malaysia takaful by collecting data from Department of Statistics Malaysia, Economic Intelligent Unit and International Monetary Fund Statistic. Used the time series data for the period of 1985 until 2004. The study has been done using time series analysis available in STATA software. This study also employs the Cointegration test and Vector Error Correction Model (VECM) to see whether General takaful contribution has short-run and long-run run relationship with all the economic variables. This study found that two independent variables which are GDP and Stock market are significant in long run relationship. This paper also highlight the relationship among the variables when GDP is positive relationship, while inflation and stock market have negative relationship with General takaful contribution. While, to answer the objective of this study, GDP is the most dominant variable.